Computer use attitudes, knowledge and skills, habits and methods of preschool teachers - UYANIK, GÜLDEN (ELSEVIER SCIENCE BV, 2011)
This study aims to examine the computer use attitudes, knowledge-skills, habits and methods of preschool teachers with respect to several variables. Participants were 127 teachers who were working at 24 state and private schools in 8 different districts of Istanbul in 2009. The measurement tool used in the study was developed from an instrument by Qui Chen and Chang (2003). When teachers' computer use attitudes, knowledge-skills, habits and methods were studied with respect to their institution, a significant difference was found in the knowledge-skills and habits subdimensions. When they were studied in relation to teachers' years in the profession, a significant difference was found in the attitude subdimension; and when they were studied in relation to providing half or full day instruction, a significant difference was found in the habit and method subdimensions. (p<0,05) Keywords: Preschool teacher, Computer use (C) 2010 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the Guest Editor.
Keywords: Preschool teacher; Computer use